Unpaid work and the economy : gender, time-use and poverty - Antonopoulos, Rania, 1960-; Hirway, Indira (Palgrave Macmillan, 2009)
Unpaid Work is increasingly recognized for its contributions to the well-being of society, it is seen as an organic component of the economic system. Predominantly in developing countries, much of the provisioning of basic needs and other conveniences of life occur beyond the boundaries of market transactions. This book combines theoretical, technical and policy-orientated discussion that reveals the need to incorporate unpaid work in economic analysis, specifically in the context of poverty and gender equality. Individual chapters investigate the intersections of income poverty, unpaid work and women's overtaxed time, the research focuses on three significant regions: Africa, Latin America and Asia. The contributors create thoughtful and provocative arguments, building upon the existing literature and synthesizing diverse strands of research on time-use surveys, to make concrete policy recommendations for development strategies. It is a great resource for policy makers, postgraduates and students interested in development studies, Gender studies and Women's studies.